2000
DOI: 10.1358/dot.2000.36.1.566627
|View full text |Cite
|
Sign up to set email alerts
|

Lornoxicam, a new potent NSAID with an improved tolerability profile

Abstract: Lornoxicam is a member of the oxicam group of nonsteroidal antiinflammatory drugs (NSAIDs). Oxicams have potent antiinflammatory and analgesic effects, but their use is associated with a high risk of gastrointestinal adverse effects. Lornoxicam has been shown to be at least as effective as comparative NSAIDs and more effective than 10 mg morphine when used at doses > or = 8 mg to control pain after oral surgery. In addition, oral doses of lornoxicam of 16-24 mg daily have been more effective than tramadol 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 0 publications
1
56
1
3
Order By: Relevance
“…19 Lornoxicam is a potent new NSAID of the oxicam class. 3,4 Previous studies with lornoxicam 8 mg have shown it to be as effective as meperidine 50 mg 5 or tramadol 50 mg 20 after various surgical procedures. In another study, Trampitsch et al 21 determined that lornoxicam administered preemptively appears to improve the quality of postoperative analgesia, and leads to reduced consumption of opioid analgesics postoperatively in patients undergoing gynecological operations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Lornoxicam is a potent new NSAID of the oxicam class. 3,4 Previous studies with lornoxicam 8 mg have shown it to be as effective as meperidine 50 mg 5 or tramadol 50 mg 20 after various surgical procedures. In another study, Trampitsch et al 21 determined that lornoxicam administered preemptively appears to improve the quality of postoperative analgesia, and leads to reduced consumption of opioid analgesics postoperatively in patients undergoing gynecological operations.…”
Section: Discussionmentioning
confidence: 99%
“…5 The most frequent adverse effects were dizziness, abdominal pain, headache, and vomiting. [3][4][5] Postoperative nausea and vomiting after thyroid surgery is especially common, with previous studies reporting a rate of 51% to 76%. [30][31][32] Similarly in our study, the most common adverse effect in the study groups were PONV, and we determined a decrease in adverse effects associated with opioid consumption in the combination group, demonstrating that a multimodal analgesic approach using adjunctive drugs reduces the need for opioid analgesic and decreases adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its analgesic activity is comparable to that of opioids. High therapeutic potency is indicated in low doses, with a reduced risk of side eff ects (6)(7)(8). Preliminary research, which requires further confi rmation, suggest that lornoxicam may be a better alternative or adjunctive therapy to opioid analgesics in the treatment of moderate to severe pain (9,10).…”
Section: Research Articlementioning
confidence: 99%
“…The plasma half-life is longer than other oxicams, and for this reason, it has fewer adverse effects [7]. In experimental studies, it has been shown that lornoxicam plays a role in decreasing hypersensitivity by causing antinociception via spinal COX inhibition [8].…”
Section: Introductionmentioning
confidence: 99%